Local Cultural Acculturation in the Practice of Nazar in Bulukumba Regency: A Study of the Angnganro Tradition from an Islamic Law Perspective - Widyani, Sri; Mulya A., M. Alyan; Nurafni, Nurafni; Basir, Muhammad Rendiyan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The phenomenon of cultural and religious acculturation in Indonesian society is often reflected in local rituals that are rich in religious meaning, one of which is the Angnganro tradition among the Kajang people in Bulukumba Regency, South Sulawesi. This study aims to analyze the form of the Angnganro tradition and examine the ritual practice from the perspective of Islamic law, particularly in relation to its status as a form of vow or expression of gratitude for the fulfillment of prayers. This study uses a qualitative method with a sociological approach to law in the context of field research. Data was collected through participatory observation, in-depth interviews with traditional and religious leaders, and documentation of rituals, then analyzed in three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that Angnganro is a collective ritual performed by the community as an expression of gratitude for recovery from illness, safety from disaster, or success in achieving a specific goal. This ritual is centered in a sacred forest area and led by a traditional leader (Amma Toa), with a series of preparations that can last for months, culminating in seven consecutive days involving extended families and traditional communities. From an Islamic legal perspective, this practice can be categorized as a form of ghairu mahdhah worship which is mubah, as long as it does not contain elements of shirk, bid'ah dhalalah, or violations of the principles of tawhid. Research confirms that the Angnganro tradition is a form of local cultural acculturation and an expression of religiousness that is acceptable in Islamic jurisprudence, provided that the practice remains based on the principle of tawhid and does not conflict with sharia law.